MINYAK ATSIRI DAUN TENGGULUN (Protium javanicum Burm.F.) SEBAGAI REPELAN NYAMUK DEMAM BERDARAH (Aedes aegypti) - Gusti Ayu Primandari Utami; Sri Rahayu Santi; Ni Made Puspawati (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
Tenggulun leaves (Protium javanicum Burm.F.) have been used traditionally as a medicine and insecticide. Activity test of essential oils from Tenggulun leaves as repellent against Aedes aegypti was done at concentrations of 7.5%, 15%, 20%, and 40% in 96% ethanol to determine its effectiveness. The essential oils were obtained by steam distillation methods, while the repellent activity test was conducted using Aedes aegypti adult females. Isolation of 12 kg fresh tenggulun leaves using steam distillation yielded 0.07% yellowish oils (13.7 mL) with the density of 0.8774 g/mL and sour sting smell. Gas chromatogram of the essential oils indicated that there were 13 compounds and identification of each compounds based on their mass spectra suggested that the compounds were ?-pinene (16.85%), myrcene (1.53%), ?-phellandrene (45.34%), p-cymene (5.60%), limonene (15.70%), ?-ocimen (0.34%), bicyclogermacrene (1.61%), ?-elemene (2.27%), ?-caryophyllene (7.90%), ?-humulene (0.88%), germacrene (1.50%), spathulenol (0.23%), caryophyllene oxide (0.24%). The repellent test result analyzed by One Way ANOVA indicated that at each concentration of the essential oils given showed significant differences during 6 hours treatment. Furthermore Tukey HSD test result showed that the essential oils at concentration of 40% revealed repellent activity which was comparable to positive control at the start of the test until the fifth hour of testing. Four of the compounds which are ?-pinene, myrcene, limonene and ?-caryophyllene have been known to have activity as repellent against mosquitoes.